Multirobot navigation functions II: towards decentralization - Loizou, Savvas; Dimarogonas, Dimos V.; Kyriakopoulos, Kostas J. (My University, 2006)
This is the second part of a two part paper regarding Multirobot Navigation Functions. In this part, we discuss extensions of the centralized scheme presented in the first part, towards decentralization concepts. Both holonomic and nonholonomic kinematic models are considered and the limited sensing capabilities of each agent are taken into account. An extension to dynamic models of the agents' motion is also included. The conflict resolution as well as destination convergence properties are verified in each case through nontrivial computer simulations.
Keywords: Robots; Computer simulation; Navigation